Obesity is a significant susceptibility factor for idiopathic AA amyloidosis - Blank, Norbert; Hegenbart, Ute; Dietrich, Sascha; Brune, Maik; Beimler, Jörg; Müller-Tidow, Carsten; Lorenz, Hanns-Martin; Schönland, Stefan (Amyloid, 2018)
Background: To investigate obesity as susceptibility factor in patients with idiopathic AA amyloidosis.Methods: Clinical, biochemical and genetic data were obtained from 146 patients with AA amyloidosis. Control groups comprised 40 patients with long-standing inflammatory diseases without AA amyloidosis and 56 controls without any inflammatory disease.Findings: Patients with AA amyloidosis had either familial Mediterranean fever (FMF) or long-standing rheumatic diseases as underlying inflammatory disease (n = 111, median age 46 years). However, in a significant proportion of patients with AA amyloidosis no primary disease was identified (idiopathic AA; n = 37, median age 60 years). Patients with idiopathic AA amyloidosis were more obese and older than patients with AA amyloidosis secondary to FMF or rheumatic diseases. Serum leptin levels correlated with the body mass index (BMI) in all types of AA amyloidosis. Elevated leptin levels of more than 30 µg/l were detected in 18% of FMF/rheumatic + AA amyloidosis and in 40% of patients with idiopathic AA amyloidosis (p = .018). Finally, the SAA1 polymorphism was confirmed as a susceptibility factor for AA amyloidosis irrespective of the type of the disease.Conclusions: Obesity, age and the SAA1 polymorphism are susceptibility factors for idiopathic AA amyloidosis. Recent advances in treatment of FMF and rheumatic disorders will decrease the incidence of AA amyloidosis due to these diseases. Idiopathic AA, however, might be an emerging problem in the ageing and increasingly obese population.
Gesehen am 12.09.2019